El neokantismo en el joven Heidegger - CAZZANELLI, Stefano (Revista de Filosofía, 2010)
In this article we intend to analyze Heidegger’s early courses and writings, trying to explain the reasons of his progressive departure from the neokantian field towards the acquisition of the phenomenological method. We will dedicate special attention to the comparison with the work of Emil Lask, a fundamental thinker for the genesis of Heidegger’s philosophy. The ending point of our path will be the outline of Heidegger’s reasons to consider that a hermeneutic approach to phenomenology is necessary.
Keywords: Lask; Neokantianism; Heidegger; pre-theoretical; Value; Validity; Ought; Theleological method; Hermeneutics; Phenomenology